Prognostic value of cancer-related fatigue at the end of radiotherapy for overall survival ≥ 10 years in women with breast cancer - Heumann, Philipp; Benner, Axel; Behrens, Sabine; Chang-Claude, Jenny; Seibold, Petra Beate (Breast cancer research, 2025)
Cancer-related fatigue (CRF) is a common symptom in breast cancer patients and survivors, which can substantially impair quality of life. Previous studies suggested that CRF may be associated with poorer survival outcomes, but had limited follow-up duration or insufficient adjustment for established prognostic factors. The aim of this analysis was to assess the prognostic value of CRF at the end of radiotherapy for overall survival in a cohort of women with breast cancer with a median follow-up time of 19 years.
Gesehen am 29.09.2025